The Wireless Threat to Fixed Broadband Services - Pugh, Nigel (Journal of Telecommunications and the Digital Economy, 2019)
This paper provides results from a survey of broadband customers in Australia in November 2017. Respondents included both NBN customers and non-NBN broadband customers. The survey showed an increasing acceptance of mobile broadband, in line with other market trends, but identified significant dissatisfaction – one quarter of mobile broadband respondents and about one third of fixed broadband respondents – with current services. Factors that may affect a decision to switch from fixed to mobile broadband, or vice versa, included price, reliability, bundling of phone with broadband, and the capability of streaming video on demand. Negative perceptions of the NBN are also significant. Overall, we identify that about 30% of existing fixed broadband households would consider switching to a wireless broadband service. We also note the future rollout of 5G wireless service and the resultant market positioning of telcos, which may support further positive perceptions of wireless broadband.